A conditional process model of the effect of mindfulness on 800-m personal best times through pain catastrophising - Jones, M. I.; Parker, J. K. (Journal of Sports Sciences, 2016)
The purpose of this study was to examine the relationship between mindfulness and 800-m personal best (PB) times through pain catastrophising and to see whether the magnitude and direction of the relationship depended on gender. One hundred and nine participants reported their gender, completed measures of mindfulness (MAAS) and pain catastrophising (PCS) and reported PB 800 m times that were standardised based on current world records. Results revealed moderate-sized relationships between the predictor variables and standardised 800 m PB. The size of these relationships reduced after we controlled for gender. The follow-up, conditional process analysis - revealed significant direct and indirect effects that confirmed that pain catastrophising partially mediated the relationship between mindfulness and 800 m PB and that gender moderated the indirect paths. The indirect path between mindfulness and pain catastrophising was consistent with existing literature. However, the path between pain catastrophising and standardised 800 m PB was positive for females and negative for males. The different direction of the relationship could suggest that pain catastrophising could be performance enhancing for females.